Challenges and Strategies for the Inclusion of Post-Quantum Algorithms in ICP-Brasil - Milanez, Arthur G. C.; Souza, Victor L. de; Pieri, Giovani; Martina, Jean (Companion Proceedings of the Brazilian Symposium on Cybersecurity (SBSeg); 2025: Companion Proceedings of the 25th Brazilian Symposium on CybersecurityDO - 10.5753/sbseg_estendido.2025.14942, 2025)
The article discusses the challenges and strategies for adapting certificate management software used in ICP-Brasil to post-quantum cryptography, in light of the threat posed by quantum algorithms such as Shor’s, which compromise the security of current systems. It presents a practical study on updating the Certificate Management System (SGC) to support post-quantum algorithms, highlighting regulatory difficulties. The work details the project phases, from research and training to integration and testing with HSMs. Finally, it underscores the importance of crypto agility and the need for interoperability tests and studies on smartcards to ensure the secure continuity of ICP-Brasil in the post-quantum scenario.